1991
DOI: 10.1055/s-2007-999417
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nifedipine and Ritodrine for the Treatment of Preterm Labor

Abstract: Treatment of preterm labor with beta-sympathomimetics has been questioned because of the many maternal and fetal complications associated with its use. Nifedipine, a calcium antagonist, has been shown to suppress uterine activity in vitro and in vivo. A randomized prospective study was performed to compare the efficacy of nifedipine to ritodrine in the suppression of preterm labor. Data obtained from 42 women, of which 19 were randomized to the ritodrine group and 23 to the nifedipine group, were analyzed. Rit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
1
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(33 citation statements)
references
References 0 publications
4
25
1
3
Order By: Relevance
“…Various studies have compared ritodrine with nifedipine and found that both are equally effective in suppressing preterm labor but side effects were significantly less with nifedipine [8][9][10][11][12]. In our study also no significant difference was noted in maternal and neonatal side effects but less side effects were noted in nifedipine group.…”
Section: Discussionsupporting
confidence: 52%
“…Various studies have compared ritodrine with nifedipine and found that both are equally effective in suppressing preterm labor but side effects were significantly less with nifedipine [8][9][10][11][12]. In our study also no significant difference was noted in maternal and neonatal side effects but less side effects were noted in nifedipine group.…”
Section: Discussionsupporting
confidence: 52%
“…564 The review of inhibition of threatened preterm labour with calcium channel blockers 565 included 12 RCTs. [566][567][568][569][570][571][572][573][574][575][576][577] Updating the searches retrieved a further five RCTs. [578][579][580][581][582] Further details of the review can be found in Appendix 6, Table 133.…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…The quality of the included studies is generally good (Figure 194). Calcium channel blockers used were nifedipine and nicardipine and comparators were magnesium sulphate, 569,574,580,581 a betamimetic (ritodrine, terbutaline, salbutamol), 566-568,570-573, [575][576][577][578][579] and an oxytocin antagonist (atosiban). 582 No placebo-controlled trials were found.…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
See 1 more Smart Citation
“…Several randomized, controlled trials have compared the efficacy of calcium channel blockers, usually nifedipine and betamimetics. Although most trials had important methodological limitations, and conclusions varied regarding effectiveness (most reporting similar tocolysis [16][17][18][19][20] and some suggesting the superiority of nifedipine [21,22], all reported a better side effect profile with nifedipine with fewer women requiring cessation of therapy due to adverse events [6,[21][22][23][24].…”
mentioning
confidence: 99%